IGLESIAS INDECENTES Y SANTOS PARA LOS POBRES LAS CONDICIONES MATERIALES DEL CULTO CATÓLICO EN EL OCCIDENTE DEL VALLE CENTRAL DE COSTA RICA 1777-1850 - Rodríguez Dobles, Esteban (2013)
This paper aims to establish the development and expansion of church infrastructure. On the other hand, seeks to complement this picture with evidence related to the cult of the saints to set some features on Catholic beliefs. It shows that poverty in the region was one of the reasons to explain why Catholic worship had some uniqueness.